A titanium-zirconium bimetallic oxide catalyst for enhancing carbon dioxide desorption and its application

By synthesizing titanium-zirconium bimetal oxide catalysts, the problem of insufficient catalytic activity and thermal stability in the prior art is solved, efficient CO2 desorption is achieved, energy consumption is reduced, and low cost and good stability is achieved.

CN114160113BActive Publication Date: 2025-04-08NANJING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111486705.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-07
Publication Date
2025-04-08
Estimated Expiration
2041-12-07

AI Technical Summary

Technical Problem

In the prior art, the catalyst catalytic activity and thermal stability of heterogeneous catalytic CO2 desorption are insufficient, resulting in high energy consumption of CO2 desorption and complex equipment.

Method used

By synthesizing a titanium-zirconium bimetal oxide catalyst, a catalyst with a high specific surface area and rich surface OH groups is prepared by reacting soluble metal titanium salt and zirconium salt with urea.

Benefits of technology

The CO2 desorption amount of CO2 amine-rich solvent is increased, and the CO2 desorption energy consumption is reduced. The catalyst preparation method is simple, low-cost and has good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114160113B_ABST
    Figure CN114160113B_ABST
Patent Text Reader

Abstract

The present invention discloses a titanium zirconium bimetallic oxide catalyst for enhancing carbon dioxide desorption and its application, belonging to the technical field of carbon dioxide capture. The preparation method of the titanium zirconium bimetallic oxide catalyst comprises the following steps: (1) dissolving a soluble metal titanium salt and urea in water to obtain a mixed solution A; (2) dissolving a soluble metal zirconium salt and urea in water to obtain a mixed solution B; (3) mixing the mixed solutions A and B to obtain a mixed solution C, heating the mixed solution C for reaction, cooling and filtering to obtain a precipitate D; (4) washing, drying, calcining and grinding the precipitate D to obtain the titanium zirconium bimetallic oxide catalyst. The catalyst of the present invention can be used to catalyze the regeneration process of a carbon dioxide-rich amine solvent, and the regeneration temperature can be reduced to below 100°C. Compared with the condition without using a catalyst, the total carbon dioxide desorption amount can be effectively increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon dioxide capture, and in particular relates to a titanium zirconium bimetallic oxide catalyst for enhancing carbon dioxide desorption and an application thereof. Background Art

[0002] Due to the increasing demand for fossil fuels, a large amount of CO2 is emitted into the atmosphere, causing serious damage to the earth's climate and ecosystem. As a simple CO2 capture technology, amine-based solution CO2 absorption has been successfully applied in coal-fired plants. Monoethanolamine (MEA) has become one of the most widely used chemical absorbents due to its significant advantages such as low price, large absorption capacity, fast absorption rate, low toxicity, moderate viscosity, good chemical stability, and low foaming. However, the huge energy consumption caused by excessive heat load during CO2 desorption and the complicated equipment caused by excessive reaction time have seriously hindered its industrial development. Therefore, it is particularly important to seek efficient and energy-saving CO2 desorption methods.

[0003] In recent years, the use of solid acid catalysts to catalyze solvent regeneration has become a key research direction for reducing the energy consumption of CO2 desorption. At present, the catalysts used for heterogeneous catalytic desorption of CO2 and recovery of amine solutions mainly include molecular sieves, transition metal oxides, solid superacid catalysts, and carrier-loaded superacid catalysts. The above catalysts can effectively reduce the desorption temperature from 120-150°C to below 100°C, increase the CO2 desorption rate of 5M CO2-rich MEA solvent, and reduce the energy consumption of solvent regeneration. However, the research on using solid acid catalysts to reduce the regeneration energy consumption of amine solvents and improve the CO2 desorption kinetics is still in its infancy and is limited to a few catalysts. The regeneration energy consumption of CO2-rich amine solvents still needs to be further reduced. Therefore, it is crucial to develop and design new and efficient solid acid catalysts for the catalytic desorption of CO2-rich amine solvents.

[0004] Due to its strong surface acidity, ZrO2 is used in the regeneration process of CO2-rich alcohol amine solution. 2- / ZrO2 was added to 5M MEA rich solution, and the CO2 desorption amount increased by 25.3% and 10.59% compared with the control group, and the heat load of the desorption process was significantly reduced (Liang et al. Industrial & Engineering Chemistry Research 56 (2017): 7656-7664, Baek et al. ACS Sustainable Chemistry & Engineering 6 (2018): 12079-12087). However, as a single metal oxide, ZrO2 has a small specific surface area, irregular pore size and easy deactivation, which is not conducive to its application in high-temperature catalytic desorption process. On the other hand, ZrO2 series catalysts have problems such as loss of active components, destruction of structural stability and reduced chemical stability during long-term catalysis (Xing et al. Environmental Science & Technology 55 (2021): 11216–11224). Therefore, it is urgent to synthesize a CO2 catalytic desorption catalyst with strong stability.

[0005] Doping ZrO2 with cheap and environmentally friendly TiO2 can form a titanium-zirconium bimetallic oxide catalyst or environmental composite material with better catalytic performance and stability. The Chinese patent application number is CN201710970014.X, and the application with the publication date of January 12, 2018 discloses a spherical mesoporous solid acid-base bifunctional catalyst and its preparation method and application. In the method, the spherical mesoporous solid acid-base bifunctional catalyst is a TiO2-ZrO2 composite metal oxide, wherein the molar ratio of Ti to Zr is 0.43 to 2.33:1, and the TiO2-ZrO2 crystal form is amorphous and has a maximum acid content. The catalyst is prepared by using hexadecylamine as a porogen, and titanium and zirconium alcohol salts are hydrolyzed and condensed into TiO2-ZrO2 gel, which is dried and calcined at high temperature. The titanium source and zirconium source used in the invention are titanium and zirconium alcohol salts, and additional raw materials such as hexadecylamine and stabilizers need to be added. The preparation cost is relatively expensive, and the preparation process is relatively complicated and time-consuming.

[0006] Based on the existing technical defects, in the field of CO2 capture technology, there is an urgent need to invent a heterogeneous catalyst with better catalytic desorption performance, simple preparation process and good stability. Summary of the invention

[0007] 1. Problem to be solved

[0008] In view of the problem that the catalytic activity and thermal stability of catalysts for heterogeneous catalytic CO2 desorption in the prior art need to be improved, the present invention further improves the desorption performance of CO2-rich amine solvents and reduces the energy consumption of CO2 desorption by synthesizing titanium-zirconium bimetallic oxide catalysts.

[0009] 2. Technical solution

[0010] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0011] A titanium-zirconium bimetallic oxide catalyst for enhancing carbon dioxide desorption, the preparation method comprising the following steps:

[0012] (1) dissolving a soluble metal titanium salt and urea in water to obtain a mixed solution A;

[0013] (2) dissolving a soluble metal zirconium salt and urea in water to obtain a mixed solution B;

[0014] (3) Mixing the mixed solutions A and B to obtain a mixed solution C, heating the mixed solution C for reaction, cooling and filtering the mixed solution to obtain a precipitate D;

[0015] (4) The precipitate D is washed with water, dried, calcined, and ground to obtain the titanium-zirconium bimetallic oxide catalyst.

[0016] Preferably, in the titanium-zirconium bimetallic oxide catalyst, the molar ratio of titanium to zirconium is (1-9):3.

[0017] Preferably, the specific surface area of ​​the titanium-zirconium bimetallic oxide catalyst is 70 to 200 m 2 ·g -1 Larger surface area and pore volume can increase the contact area of ​​reactants on the catalyst, thereby improving the catalytic effect.

[0018] Preferably, the hydroxyl content of the titanium-zirconium bimetallic oxide catalyst is 4.3×10 20 ~6.2×10 20 OH / g. Abundant surface OH groups are beneficial to MEAH + 、MEACOO - and HCO3 - / CO3 2- The reactants are adsorbed onto the surface of the catalyst, thereby catalyzing the desorption of CO2.

[0019] Preferably, the molar ratio of the soluble metal titanium salt or the soluble metal zirconium salt to urea is 1:5.

[0020] Preferably, in step (1), the soluble metal titanium salt is one of titanium sulfate, titanium chloride, titanium nitrate and titanium oxysulfate.

[0021] Preferably, in step (2), the soluble metal zirconium salt is one of zirconium sulfate, zirconium chloride, zirconium nitrate and zirconium oxychloride.

[0022] Preferably, in step (3), the heating reaction temperature is 150-180° C., and the reaction time is 18-20 h.

[0023] Preferably, in step (4), the drying time is not less than 24 hours; the calcination temperature is 300-600° C., and the calcination time is not less than 4 hours.

[0024] The present invention also provides an application of the titanium-zirconium bimetallic oxide catalyst in the catalytic desorption process of an amine solvent rich in carbon dioxide.

[0025] Preferably, the amine solvent includes one or more of ethanolamine (MEA), diethanolamine (DEA), triethanolamine (TEA), N-methylmonoethanolamine (MDEA), and 2-amino-2-methyl-1-propanol.

[0026] Preferably, the titanium-zirconium bimetallic oxide catalyst is used in an amount of 0.5-1.5 wt %, the desorption temperature is 80-99° C., and the stirring speed is 300-500 rpm.

[0027] 3. Beneficial effects

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) Compared with single metal oxides TiO2 and ZrO2, the titanium-zirconium bimetallic oxide catalyst of the present invention can increase the CO2 desorption of CO2-rich ethanolamine solution by 15% to 35%; compared with the solution without catalyst, the CO2 desorption of CO2-rich ethanolamine solution can be increased by 30% to 54%, thereby reducing the energy consumption of CO2 desorption; and the titanium-zirconium bimetallic oxide catalyst has a simple preparation method and low catalyst cost;

[0030] (2) The titanium-zirconium bimetallic oxide catalyst prepared in the present invention has excellent catalytic desorption performance, which may be due to the fact that the TiO2-ZrO2 bimetallic oxide has more surface hydroxyl groups than pure TiO2 and ZrO2; among them, as shown in Example 1, the OH group content of TZ1 / 1 is the highest, which is 6.13×10 20 OH / g, which is 1.7 and 2.2 times that of TiO2 and ZrO2 respectively; the abundant surface OH groups are beneficial to MEAH + 、MEACOO - and HCO3 - / CO3 2- The reactants are adsorbed onto the surface of TZ1 / 1, thus showing excellent catalytic CO2 desorption activity;

[0031] (3) The titanium-zirconium bimetallic oxide catalyst prepared by the present invention has good stability. Compared with single metal ZrO2, its catalytic desorption activity remains basically unchanged after being recycled 5 times for CO2 desorption from CO2-rich ethanolamine solution, and it can be recycled, greatly reducing the application cost of the CO2 desorption catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The desorption performance diagram of CO2-rich ethanolamine solution catalyzed by five catalysts prepared in Comparative Example 1 and Example 1;

[0033] Figure 2 In-situ infrared images of the catalytic desorption process of 5M MEA solution without catalyst and with TZ1 / 1 catalyst;

[0034] Figure 3 XRD patterns and TEM (including SAED) patterns of the five prepared catalysts;

[0035] Figure 4 are SEM images of the five prepared catalysts;

[0036] Figure 5 N2 adsorption-desorption isotherms and pore size distribution diagrams of the five prepared catalysts;

[0037] Figure 6 NH3-TPD and TGA graphs of the five prepared catalysts;

[0038] Figure 7 The relationship between the properties (specific surface area, pore volume, acidity and OH content) of the five prepared catalysts and their catalytic desorption performance;

[0039] Figure 8 This is a graph of the 5-cycle desorption performance of ZrO2 in Comparative Example 1 and TZ1 / 1 catalyst in Example 1. DETAILED DESCRIPTION

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0041] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0042] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.

[0043] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values ​​or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values ​​and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.

[0044] The present invention is further described below in conjunction with specific embodiments.

[0045] Example 1

[0046] Preparation of titanium-zirconium bimetallic oxide catalyst:

[0047] (1) Dissolve 1.6 g of TiOSO4·xH2SO4·yH2O and 3 g of urea in 50 mL of ultrapure water and stir to obtain a mixed solution A.

[0048] (2) Dissolve 3.2 g ZrOCl2·8H2O and 3 g urea in 50 mL ultrapure water and stir to obtain mixed solution B.

[0049] (3) Mix the mixed solutions A and B, stir them evenly to obtain a mixed solution C, transfer the mixed solution C to a 250 mL polytetrafluoroethylene reactor, react at 150° C. for 20 h, and cool naturally to room temperature to obtain a precipitate D.

[0050] (4) The mixed solution treated in step (3) was centrifuged to separate the solid, washed with ultrapure water for 3 times, and vacuum dried for 36 hours. The dried sample was calcined at 600°C for 4 hours at a heating rate of 5°C / min, and the sample was ground after natural cooling. The obtained white powder is a titanium-zirconium bimetallic oxide with a titanium-zirconium molar ratio of 1:1, denoted as TZ1 / 1.

[0051] The molar ratio of titanium salt, zirconium salt and urea was kept at 1:5, and titanium-zirconium bimetallic oxide catalysts with titanium-zirconium molar ratios of 1:3 and 3:1 were synthesized by changing the molar ratio of the added titanium salt and zirconium salt, which were recorded as TZ1 / 3 and TZ3 / 1, respectively.

[0052] Comparative Example 1

[0053] For comparison, the other steps are the same as those in Example 1, except that only the titanium salt of step (1) or only the zirconium salt of step (2) is added, and the other steps remain unchanged to synthesize pure TiO2 and ZrO2 catalysts.

[0054] Example 2

[0055] Figure 1 The catalytic performance diagram of the regeneration of 5M CO2-rich MEA solution (CO2 loading of 0.53 mol CO2 / molamine) catalyzed by five catalysts, TiO2, ZrO2 prepared in Comparative Example 1 and TZ1 / 1, TZ1 / 3, and TZ3 / 1 prepared in Example 1. Among them, the catalyst dosage is 1g / L. The results show that the addition of catalyst can increase the CO2 desorption rate to varying degrees, desorb more CO2 at a lower desorption temperature, and reduce the energy consumption of solvent regeneration. Compared with single TiO2 and ZrO2, titanium zirconium bimetallic oxide catalysts (TZ1 / 1, TZ1 / 3, TZ3 / 1) have better catalytic performance, among which TZ1 / 1 catalyst has the best catalytic desorption effect. Compared with no catalyst, TZ1 / 1 catalyst increased the CO2 desorption amount by 54% within 180min. This may be due to the high specific surface area and rich surface acidity of TZ1 / 1 catalyst.

[0056] Figure 2 In situ infrared images of the catalytic desorption process of 5M CO2-rich MEA solution under the action of TZ1 / 1 catalyst (a) and without catalyst (b). -1 The peak at corresponds to carbamate (MEACOO - ) - Asymmetric stretching, symmetric stretching, and N-COO - Stretching vibration. 1388cm -1 The peak at is carbonate (CO3 2- ) double degenerate stretch, 1360cm -1 The peak at is bicarbonate (HCO3 - ) symmetrical stretch. 955cm -1 The CNH out-of-plane swing and C-NH2 twist at 1634 cm correspond to the free MEA molecule. -1 NH swing and 1069cm -1 The CN bond stretching at corresponds to the protonated MEA molecule (MEAH + ). In a CO2-rich MEA solution without a catalyst, MEACOO - and MEAH + The peak intensities of these substances, especially MEAH +The peak of MEACOO was significantly reduced under the action of the catalyst, which confirmed that the introduction of TZ1 / 1 catalyst - Endothermic decomposition and MEAH + The deprotonation of CO2 is greatly improved. Therefore, the TZ1 / 1 catalyst can significantly improve the CO2 desorption rate and thus reduce the energy consumption of CO2 capture.

[0057] Example 3

[0058] The five catalysts TiO2, ZrO2 prepared in Comparative Example 1 and TZ1 / 1, TZ1 / 3 and TZ3 / 1 prepared in Example 1 were characterized. Figure 3 The XRD patterns of the five samples are shown in Figure 2. As can be seen from the figure, pure TiO2 and ZrO2 show obvious characteristic peaks of anatase and baddeleyite, respectively. The XRD pattern of TZ3 / 1 still shows the characteristic peaks of anatase, and no relevant diffraction signals of ZrO2 are observed, indicating that the structure of anatase is still retained in the presence of a small amount of Zr doping. However, the diffraction peak of TZ3 / 1 shifts to a lower angle and the peak intensity weakens. The strongest diffraction peak shifts from 25.1° to 24.9°, indicating that the anatase lattice is distorted. Similarly, TZ1 / 3 is still a crystal structure of ZrO2, but the peak intensity is greatly weakened. When the molar ratio of Ti / Zr is 1, no obvious characteristic peaks are observed in the XRD pattern of TZ1 / 1, showing an amorphous structure. This is mainly due to the complete destruction of the lattice structure and the formation of Ti-O-Zr bonds. No lattice fringes and diffraction patterns were observed in the TEM images of TZ1 / 1, indicating that the TZ1 / 1 catalyst maintained an amorphous structure, which was consistent with the XRD results, which might be caused by the distortion of crystallinity after the mutual incorporation of Zr and Ti.

[0059] The SEM images of the five catalysts prepared are shown in Figure 4 As shown in the figure, TiO2, TZ3 / 1 and TZ1 / 1 have uniform morphology, are spherical, and have a size of 3 to 6 μm. When the molar fraction of Zr is greater than 50%, such as TZ1 / 3 and ZrO2, the catalyst has an irregular block structure with a size range of 5 to 10 μm. This shows that the size and morphology of TZO materials can be adjusted by changing the molar ratio of Ti / Zr. A small amount of Zr doped into TiO2 will lead to the formation of regular spheres, while a higher Zr doping amount will lead to the growth of irregular clusters. The irregular block structure of ZrO2 may cause its structure to be destroyed and the active components to be lost during high-temperature catalytic desorption, resulting in catalyst deactivation and reduced stability.

[0060] The N2 adsorption-desorption isotherms of the five prepared catalysts are shown in Figure 5(a) is shown, and the specific surface area, pore volume and pore size are shown in Table 1. The results show that compared with single metal oxides, titanium-zirconium doping can significantly increase the specific surface area of ​​the material. Among them, TZ1 / 1 has the largest specific surface area of ​​183.66 m 2 g -1 , while the specific surface areas of pure TiO2 and ZrO2 are only 53.56 and 35.28 m 2 g -1 In addition, the doping of Ti and Zr can form a larger pore volume. The pore volume of TZ1 / 1 is 0.444cm 3 g -1 , which is 157% and 83% larger than pure TiO2 and ZrO2, respectively. Figure 5 As shown in (b), compared with other catalysts, TZ1 / 1 catalyst also exhibits a uniform pore size distribution. The larger surface area and pore volume of TZ1 / 1 can increase the contact area of ​​the reactants on the catalyst, thereby improving the catalytic effect.

[0061] Table 1 Physical properties of TZO catalyst

[0062]

[0063] Figure 6 (a) is the NH3-TPD curve of five catalysts. The amount of NH3 desorbed from the catalyst can be considered as the amount of acid sites on the catalyst. With the increase of the molar fraction of Zr in the titanium-zirconium bimetallic oxide catalyst, the total acid sites first increase and then decrease, and the total acid sites of the TZ1 / 1 catalyst reach the maximum value. Figure 6 The acid strength of TZ1 / 1 is 1.125 mmol / g, while the acid strengths of pure TiO2 and ZrO2 are 0.418 and 0.153 mmol / g, respectively. The abundant acid sites of TZ1 / 1 catalyst play an important role in promoting CO2 desorption kinetics and proton transfer rate. In heterogeneous catalysis, adsorption of reactants onto the catalyst surface is a prerequisite step. Studies have shown that hydroxyl groups on the surface of metal oxides play a vital role in the adsorption of reactants onto catalysts. TGA analysis was used to determine the surface hydroxyl groups of TZO catalyst ( Figure 6 (b)), and the calculation results are shown in Table 2. TiO2-ZrO2 bimetallic oxide has more surface hydroxyl groups than pure TiO2 and ZrO2. Among them, TZ1 / 1 has the highest OH group content of 6.13×10 20 OH / g, which is 1.7 and 2.2 times that of TiO2 and ZrO2, respectively. The abundant surface OH groups are beneficial to MEAH + 、MEACOO - and HCO3 - / CO3 2-The reactants are adsorbed onto the surface of TZ1 / 1, thus exhibiting excellent catalytic CO2 desorption activity.

[0064] In summary, the excellent catalytic CO2 desorption activity of TZ1 / 1 catalyst may be due to its high specific surface area and mesoporous properties, as well as strong surface acidity and abundant surface hydroxyl content.

[0065] Table 2 Surface acidity and surface hydroxyl content of TZO catalysts

[0066]

[0067] Example 4

[0068] In order to prepare efficient catalysts for CO2 capture, it is necessary to explore the influence of catalyst properties on their catalytic activity. This paper studies the correlation between CO2 desorption performance and cycle capacity and catalyst performance (including specific surface area, pore volume, total acid sites and surface hydroxyl content), such as Figure 7 As shown. Figure 7 As shown in (a) and (b), larger specific surface area and pore volume are beneficial to improving CO2 desorption performance. Larger surface area and pore volume can not only provide more active substances for the catalytic reaction, but also increase the reactant species (MEACOO - 、MEAH + 、HCO3 - ) collision and proton transfer frequency, resulting in better catalytic CO2 desorption activity. Figure 7 (c) A positive correlation between the catalyst cycle capacity and the acid sites is observed. The TZ1 / 1 catalyst exhibits the best catalytic CO2 desorption performance and the most abundant acid sites. According to the dual-site catalytic CO2 desorption mechanism, the acid sites of the catalyst are in MEACOO - The acidic sites of the catalyst can be used to absorb the adsorbed MEACOO - Protons are provided to form MEACOOH, which decomposes into MEA and CO2. The acidic sites of the catalyst can improve the efficiency of proton transfer and reduce the - The difficulty of decomposition, thereby reducing the energy consumption of CO2 desorption. The adsorption of reactants is a prerequisite for heterogeneous catalysis, and the adsorption capacity of the catalyst can be represented by its surface hydroxyl content. Figure 7 As shown in (d), the CO2 desorption activity is positively correlated with the surface hydroxyl content of the catalyst. The higher the surface hydroxyl content of the TZ1 / 1 catalyst, the more reactants such as MEACOO can be adsorbed. - and MEAH + , promoting the proton transfer of these substances, thereby improving the CO2 desorption kinetics.

[0069] Example 5

[0070] Figure 8 The figure is a graph of the desorption performance of ZrO2 in Comparative Example 1 and TZ1 / 1 in Example 1 after 5 cycles. After each CO2 catalytic desorption experiment, the separated TZ1 / 1 and ZrO2 catalysts were washed with ultrapure water and dried in an oven at 80°C for 12 hours. Figure 8 As shown in the figure, the cyclic desorption capacity of ZrO2 catalyst decreases significantly with the increase of the number of times used, and the CO2 desorption amount in the fifth desorption experiment decreases by 26.5% compared with the first desorption experiment. On the contrary, the cyclic desorption capacity of CO2 of TZ1 / 1 catalyst increases slightly in the first four cycles, which may be due to the small amount of Zr in MEA solution. 4+ and Ti 4+ The leaching of ions leads to homogeneous catalytic CO2 desorption. The CO2 cycle capacity of the TZ1 / 1 catalyst has almost no change after 5 cycle experiments. There is almost no change in the XRD and FT-IR curves of the TZ1 / 1 catalyst used 5 times and the fresh TZ1 / 1 catalyst, which shows that the TZ1 / 1 catalyst has excellent stability. The bimetallic oxide catalyst synthesized by titanium-zirconium doping has better stability than single ZrO2, which may be due to the mutual incorporation of Ti and Zr in the TZ1 / 1 catalyst into each other's lattice to form an amorphous structure and Ti-O-Zr bonds, or it may be because the more uniform spherical structure and regular pore size distribution of the TZ1 / 1 catalyst enable it to maintain a certain structural stability in CO2 catalytic desorption, avoiding the loss, deactivation and collapse of the active components.

[0071] The above content is a schematic description of the present invention and its implementation methods, which is not restrictive. What is shown in the embodiment is only one of the implementation methods of the present invention, and the actual implementation method is not limited thereto. Therefore, if a person of ordinary skill in the art is inspired by it and designs implementation methods and embodiments similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.

Claims

1. An application of a titanium-zirconium bimetallic oxide catalyst, characterized in that: The titanium zirconium bimetallic oxide catalyst is applied to the catalytic desorption process of an amine solvent rich in carbon dioxide, wherein the amount of the titanium zirconium bimetallic oxide catalyst used in the desorption process is 0.5-1.5 wt %, and the desorption temperature is 80-99° C.; The preparation method of the titanium-zirconium bimetallic oxide catalyst is as follows: S1. Dissolve TiOSO4·xH2SO4·yH2O and urea in ultrapure water and stir to obtain a mixed solution A; The content of TiOSO4·xH2SO4·yH2O is 1.6 g, the amount of urea added is 3 g, and the amount of pure water added is 50 mL; S2, dissolve 3.2 g ZrOCl2·8H2O and 3 g urea in 50 mL ultrapure water and stir to obtain mixed solution B; The content of ZrOCl2·8H2O is 3.2 g, the amount of urea added is 3 g, and the amount of pure water added is 50 mL; S3, mixing the mixed solutions A and B, stirring evenly to obtain a mixed solution C, transferring the mixed solution C to a polytetrafluoroethylene reactor, reacting at 150°C for 20 h, and naturally cooling to room temperature to obtain a precipitate D; S4, washing the precipitate D obtained in S3 with ultrapure water for 3 times, and vacuum drying for 36 h; after drying, heating from room temperature to 600°C at a heating rate of 5°C / min and calcining for 4 h, and grinding the sample after natural cooling to obtain a titanium-zirconium bimetallic oxide catalyst with a molar ratio of titanium to zirconium of 1:1; The specific surface area of ​​the titanium-zirconium bimetallic oxide catalyst is 183.66 m 2 / g, and the pore volume is 0.444 cm 3 / g, the average pore size is 33.54 nm, and the surface acidity is 1.125 mmol / g.

2. The use of a titanium-zirconium bimetallic oxide catalyst according to claim 1, characterized in that: The amine solvent includes one or more of ethanolamine, diethanolamine, triethanolamine, N-methylmonoethanolamine, and 2-amino-2-methyl-1-propanol.

Citation Information

Patent Citations

  • Spherical mesoporous solid acid-base bifunctional catalyst, preparation method and application of catalyst

    CN107570133A

  • Distillation regeneration method of amine-based carbon dioxide absorbent using metal oxide catalyst

    WO2021117912A1